Noodles, the all-in-one system for on-target efficiency analysis of CRISPR guide RNAs - Dongfa Lin; Syeda Sadia Najam; Yu Liu; Nicola Murgia; Ilya A. Vinnikov (MethodsX, 2024)
The efficiency of clustered regularly interspaced short palindromic repeats (CRISPR) guide RNA (gRNA) targeting is critical for CRISPR associated protein 9 (Cas9)-dependent genomic modifications. Here, we developed Noodles, an all-in-one system to test the on-target activity of gRNAs easily and efficiently. Single-strand annealing repair mechanism of the split luciferase gene allows a positive selection of gRNAs efficiently driving nuclease activity of Cas9 from Streptococcus pyogenes (SpCas9). Our system can reliably validate in silico-predicted gRNAs before implementing them for in vitro and in vivo applications. Altogether, Noodles might be an asset for researchers and bioengineers, saving their time and efforts, while keeping the screening efficient and sensitive. • All-in-one dual-luciferase system to easily probe on-target activity of gRNAs based on homology-directed repair mechanism. • Easy-to-subclone spCas9-based 2-plasmid system comprising Renilla luciferase for transfection efficiency control.